Evaluation of Student Feedback on Integrated vs. Traditional Curriculum in Dental Education: A Comparative Study: Evaluation of Student Feedback on Integrated vs. Traditional Curriculum - Nisa, Waqar Un; Awais, Syed Muhammad; Ahmad, Sana; Khan, Ismail Alam; Riasat, Madiha; Zaman, Raham (Pakistan Journal of Health Sciences, 2025)
Dental education benefits a lot from a well-designed curriculum. Integrated curricula now replace traditional teaching models by adding early practical learning, connecting different subjects in training, and making students a priority. The research investigates dental students’ opinions on integrated and traditional ways of presenting the curriculum in Pakistan. Objectives: To compare dental students’ perceptions of the learning environment and curriculum structure in integrated versus traditional curricula at a dental college in Mardan, Pakistan. Methods: This cross-sectional study was carried out at Bacha Khan College for the duration of 3 months. There were 182 undergraduate students in the study who were selected using stratified sampling. The study measured how students perceived the environment and curriculum with a questionnaire based on a Likert scale of 5 points. Data were analyzed in SPSS version 21.0, and p-values smaller than 0.05 were regarded as statistically significant. Results: Students in the integrated curriculum reported significantly higher satisfaction across all domains, including support for diversity (mean = 4.35 ± 0.65), academic discussions (4.50 ± 0.55), self-directed learning (4.45 ± 0.50), and preparedness for clinical practice (4.50 ± 0.45). Similarly, curriculum structure and delivery were better rated in the integrated group, with clearer objectives, earlier clinical exposure, and stronger subject integration (p<0.05). Conclusions: Students favored the integrated curriculum due to its inclusive environment, alignment of teaching with learning outcomes, and focus on critical competencies. These findings support curricular reform toward integrated models in dental education to enhance learning outcomes and professional readiness.